DEVELOPMENT OF AN INFORMATION-STRUCTURAL MODEL OF THE DESIGN PROCESSES OF ADAPTIVE CLOTHING FOR PEOPLE WITH EXTREMITY INJURIES - LUSHCHEVSKA, OLENA; BUKHANTSOVA, LIUDMYLA; KRASNIUK, LARYSA; KOVALCHUK, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The analysis of scientific literature has demonstrated that there is a lack of research focused on the design of adaptive clothing for individuals with limb injuries, fractures, or amputations. To address this gap, interviews were conducted with hospital patients suffering from arm and leg injuries. These interviews made it possible to identify and systematize consumer needs, which were subsequently considered during the stage of pre-design research. Based on the results of the consumer survey, a structured model of consumer requirements for adaptive clothing for people with limb injuries was developed. It was established that at different stages of treatment and rehabilitation, consumers have varying requirements for adaptive clothing. Consequently, three subgroups of adaptive garments were identified: hospital clothing, rehabilitation clothing, and post-rehabilitation clothing. Hospital and rehabilitation clothing are closely connected with the medical field and serve a similar purpose—providing patient care, which includes measures aimed at supporting and restoring physical strength, creating comfortable conditions for recovery, and preventing or treating complications. Post-rehabilitation clothing is intended for individuals who have completed treatment and rehabilitation in hospital settings and are in the process of adapting to their daily routines.By applying modeling methods, functional-logical models of design situations in the development of adaptive clothing were constructed. A specific design situation was determined to ensure the efficiency of the design process, and a capsule collection of men’s waist-length adaptive clothing for individuals with leg injuries and amputations was proposed. This capsule includes three items: hospital briefs, rehabilitation shorts, and post-rehabilitation trousers.Rational design and technological solutions for adaptive clothing were proposed, which involve the use of ergonomically positioned Velcro fasteners in hospital and rehabilitation garments. For the post-rehabilitation period, stylish everyday adaptive trousers in a sporty style with side zipper fasteners were developed. The proposed capsule collection of adaptive clothing contributes to facilitating adaptation to new living conditions, thereby promoting social integration and inclusion of individuals with leg injuries.
Keywords: adaptive clothing; modeling methods; adaptive clothing capsule; adaptive underwear; shorts; pants